The truth about recruiting the top talent - Fyock, Catherine D. (FTPress Delivers elements., 2011)
This Element is an excerpt from The Truth About Hiring the Best (9780132381864) , by Cathy Fyock. Available in print and digital formats. A simple plan for recruiting top talent--in any industry, at any level. If the best candidates aren't working for your organization, they are probably working for your competitor. To compete successfully for the best and brightest, first identify who your competitors are for your first-choice employees. They aren't just your competitors for market share. They could be anyone --especially when you are looking for entry-level, hourly, and clerical workers.